Morphological features and aerobic capacity in soccer players with hypermobility of joints - Yevhen Hlushchuk; Oleh Nekhanevych; Viacheslav Khomenko (Bogomolets National Medical University, 2021)
Intensification of physical loads in modern soccer requires athletes to develop a high level of general, speed and special endurance. Athletes with signs of connective tissue dysplasia, one of the most frequent manifestations of which is hypermobility of the joints, are of special interest to coaches and doctors when building training and competitive loads in football. Systematic involvement of connective tissue in the dysplastic process in hypermobility of joints can affect the development of physical qualities, physical fitness, level of functional status and aerobic performance and can be the cause of negative sports results. Failure to take into account the characteristics of such athletes can be the cause of acute physical exertion. The aim of this work was to establish the morphological features and level of aerobic productivity in football players with signs of hypermobility of the joints. To achieve this goal, the data of 46 high-class football players of the Azerbaijani national football team aged 16 to 34 were analyzed. Determination of morphometric parameters was performed using anthropometry, body composition was assessed using impedancemetry, clinical signs of joint hypermobility were diagnosed by R. Beighton criteria, aerobic performance was assessed directly using gas analysis during exercise on an exercise bike. According to the results of the study of the level of hypermobility of the joints, it was found that 56.5% of football players had normal mobility in the joints, 30.4% - moderate and 13.0% - significant hypermobility. In football players with significant joint hypermobility, the level of aerobic productivity was the lowest and was 53.3±2.5 ml/min/kg, while the rate of maximum oxygen consumption was the highest in the group with normal joint mobility (59.5±1.2 ml/min/kg). Investigating the dynamics of the value of maximum oxygen consumption in the groups, a statistically significant decrease in its value with increasing degree of hypermobility was found. Thus, in the group with normal mobility the increase in VO2 max was 5.3±0.2 ml/min/kg, in the group with moderate hypermobility - 3.7±0.2 ml/min/kg and in the group with significant hypermobility - 1,7±0.2 ml/min/kg. A study of body composition in groups divided by the level of hypermobility of the joints, indicated that the lowest level of total water was in the group with severe hypermobility. Such dynamics occurred due to a decrease in the level of extracellular fluid, which may indicate a violation of metabolic processes in the intercellular matrix. There was a statistically significant decrease in the level of maximum oxygen consumption with increasing degree of hypermobility of the joints. The difference in the response of the functional systems of the body of football players during general endurance training is proved. Establishing relationships between body composition and maximum oxygen consumption can be the basis for regulating training and competitive loads and for sports selection.